Cow's milk protein intolerance – an uncommon but important cause of hypoalbuminaemia. (24th May 2012) - Tanwar, M; Ho, P
Abstract : The predominant cause of paediatric hypoalbuminaemia is due to renal glomerular dysfunction. Cow's milk protein Intolerance (CMPI) is a gastrointestinal cause of hypoalbuminaemia with estimated prevalence between 1.2% to 17%. Whilst the majority of protein losing enteropathies are diagnosed following on from referral to gastroenterology, CMPI can often be readily diagnosed by simple blood and stool tests. We report 2 cases of CMPI seen over a one year period at a district general hospital which both presented with hypoalbuminaemia. Case 1: A previously well 10 month old boy presented with 3 weeks history of generalised oedema, pallor and a 3 month history of diarrhoea which coincided with weaning from breast to formula milk. Initial investigations revealed microcytic hypochromic anaemia (Hb 5.6 g/dl) and hypoalbuminamia (serum albumin: 18 g/l). Urine dipstick was negative for protienuria. Initial investigations including immunoglobulins and celiac screen were also negative. Stool for faecal elastase was normal. He was subsequently referred to a tertiary centre for further assessment including an upper GI endoscopy and biopsy which was unremarkable. Case 2: A previously well 10 month old girl who presented with history of generalised oedema over a one week period. She had started weaning one month before and there was no history of diarrhoea. She was pale with generalised oedema. Urine dipstick was negative for protienuria. Initial investigations revealed microcytic hypochromic anaemia (Hb 5.9 g/dl) and hypoalbuminaemia (serum albumin: 14 g/l). Coeliac screen was negative. IgE levels were raised to 107 KU/l. Stool for elastase was mildly elevated to 500 µg/g and for reducing substances was suggestive of malabsorption respectively. RAST for mixed food was strongly positive. In both cases a diagnosis of CMPI was made and resolution of hypoalbuminaemia was noted after starting hypoallergic formula. In case 1, the patient required protracted investigation following on from referral to gastroenterology. In contrast, the second patient was diagnosed simply by stool and blood tests. We suggest that children with non renal hypoalbuminaemia and anaemia associated with weaning can be managed in a district hospital with a trial of cow's milk free diet, with tertiary gastroenterology referral reserved for those who fail to respond.